АБУ АЛИ ИБН СИНО ЖИСМОНИЙ ТАРБИЯ ВА СОҒЛОМ ТУРМУШ ТАРЗИ ҲАҚИДА - Есемуратов, С.; Алланиязов, С. (SCIENCE and SOCIETY, 2016)
The article deals with the analysis of views of the great world scientist Abu Ali Ibn Sino about physical development and healthy life of people. It presents a number of medical advice given by the Eastern genius about importance of keeping healthy life from birth till death. The author of the article describes the importance of slow walking, slow and fast running from childhood till the old age.
Keywords: great scientist; gymnastic exercises; walking; running (jogging) differential exercises; heart; liver; breath; heart regime; distance; rehabilitation; miocard; heart attack; a representative of science; thinker; world progress; healthy life